A study on the metallicity gradients in the galactic disk using open clusters - Joshi, Yogesh Chandra; Deepak; Malhotra, Sagar (Frontiers in Astronomy and Space Sciences, 2024)
We study the metallicity distribution and evolution in the galactic disk based on the largest sample of open star clusters in the galaxy. From the catalog of 1,879 open clusters in the range of galactocentric distance (RGC) from 4 to 20 kpc, we investigate the variation in metallicity in the galactic disk as functions of RGC, vertical distance (Z), and ages of the clusters. In the direction perpendicular to the galactic plane, the variation in metallicity is found to follow a stepped linear relation. We estimate a vertical metallicity gradient d[Fe/H]d|Z| of −0.545 ± 0.046 dex kpc−1 for |Z| < 0.487 kpc and −0.075 ± 0.093 dex kpc−1 for 0.487 < |Z| < 1.8 kpc. On average, metallicity variations above and below the galactic plane are found to change at similar rates. The change in metallicity in the radial direction is also found to follow a two-function linear relation. We obtain a radial metallicity gradient d[Fe/H]dRGC of −0.070 ± 0.002 dex kpc−1 for 4.0 ≲ RGC ≲ 12.8 kpc and −0.005 ± 0.018 dex kpc−1 for 12.8 ≲ RGC ≲ 20.5 kpc, which clearly shows a strong variation in the metallicity gradient when moving from the inner to the outer galactic disk. The age–metallicity relation (AMR) is found to follow a steeper negative slope of −0.031 ± 0.006 dex Gyr−1 for clusters older than 240 Myr; however, there is some hint of positive metallicity age gradient for younger clusters.